(untitled) (Journal of Nepal Geological Society, 2002)
The present paper attempts to evaluate the present status of hazard mapping in Nepal and describes the case studies of landslide hazard mapping of the Lothar Khola (central Nepal) and Syangja district (western Nepal) by two different methods: 1. The rating method proposed in the Mountain Risk Engineering (Deoja et al. 1991), and 2. Bivariate Statistical method developed by the Institute of Aerospace Survey and Earth Sciences (ITC). The Netherlands (Van Westen 1997). The first method is a manual one and used to make hazard map of the Lothar Khola watershed while the second one is GIS based and was utilized to produce hazard map of the Syangja district. Potentially unstable slopes were mainly found on the slopes ranging from 26-40°, residual soil cover, and in areas underlain by the slate and phyllite. Interestingly the slope movement is high in the areas covered by forest in comparison to the cultivated slopes.